2014
DOI: 10.3389/fpsyg.2014.00196
|View full text |Cite
|
Sign up to set email alerts
|

Postdiction: its implications on visual awareness, hindsight, and sense of agency

Abstract: There are a few postdictive perceptual phenomena known, in which a stimulus presented later seems causally to affect the percept of another stimulus presented earlier. While backward masking provides a classical example, the flash lag effect stimulates theorists with a variety of intriguing findings. The TMS-triggered scotoma together with “backward filling-in” of it offer a unique neuroscientific case. Findings suggest that various visual attributes are reorganized in a postdictive fashion to be consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
79
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 60 publications
4
79
0
3
Order By: Relevance
“…13). This is in line with the proposal that illusory motion can be understood as a post-dictive perceptual phenomenon1718, in which the motion percept along the apparent motion trajectory is constructed after the stimuli have been presented. It has been further reported that perception of illusory motion is abolished when the fixation point falls on the apparent motion path, potentially because of the less precise representation of stimuli in the periphery.…”
Section: Resultssupporting
confidence: 89%
“…13). This is in line with the proposal that illusory motion can be understood as a post-dictive perceptual phenomenon1718, in which the motion percept along the apparent motion trajectory is constructed after the stimuli have been presented. It has been further reported that perception of illusory motion is abolished when the fixation point falls on the apparent motion path, potentially because of the less precise representation of stimuli in the periphery.…”
Section: Resultssupporting
confidence: 89%
“…In particular, these models describe how top-down predictions or inferences are matched to incoming sensory inputs across different levels of the cortical hierarchy. Different levels of the cortical hierarchy represent different levels of abstraction at which predictions and inferences are instantiated: Lower levels implement, for example, the continuation of regular spatial patterns behind occlusions or in the blind spot of our retina (Komatsu, 2006;Shimojo, 2014), whereas higher levels implement how we mentally represent others and their expected behaviour (Koster-Hale & Saxe, 2013). When there is a mismatch between the predicted and the received sensory inputs, a prediction-error signal is fed forward up the cortical hierarchy, which in turn evokes new or updated inferences that better match the sensory inputs.…”
Section: A Neurally Inspired Perspective On the Interpretation Of Cismentioning
confidence: 99%
“…Similar arguments have been raised in the context of simultaneity illusions, where it has been claimed that marker correspondence and not neural processing latencies determines temporal binding of visual attributes9. This view rejects the idea that event time is inferred from brain time and instead suggests a postdictive estimation of time1011.…”
mentioning
confidence: 52%